Identification and Functional Analysis of Cynoglossus semilaevis Z-Linked E3 Ubiquitin Ligase rnf34 - Lu Li; Xihong Li; Yadong Chen; Yingming Yang; Na Wang; Wenteng Xu (Animals, 2024)
The high proportion of males in C. semilaevis hinders their industrial development. The genetic ZW individual can become a pseudomale by sex reversal. And the pseudomale can produce Z-sperm (with epigenetic information to cause sex reversal) while W-sperm is absent, which leads to an even higher male proportion in offspring. Recently, with the development of transcriptomic technologies, research on spermatogenesis in C. semilaevis has been focused on the ubiquitination pathway. In this study, we analyzed the function of the ubiquitin ligase rnf34 gene on the Z chromosome. A qPCR experiment showed that its expression level in the gonad was the highest among different tissues. In the ovary, the expression gradually increased with development from 40 days post-hatching (dph) to 1.5 years post-hatching (yph). In the testis, rnf34 showed increased expression from 40 dph to 6 months post-hatching (mpf) and stabilized up until 1.5 ypf. In situ hybridization showed that the mRNA of rnf34 was mainly distributed in the germ cells of the testis and the ovary. In vivo siRNA-mediated knockdown of the rnf34 gene in male fish affected the expression of a series of genes related to sex differentiation and spermatogenesis. These results provide genetic data on the molecular mechanisms of gonadal development and spermatogenesis in C. semilaevis.